The Effects of Green Accounting Disclosure, Eco-Efficiency, and Sales Growth on Firm Value: Evidence from IDX Energy Companies, 2020–2024 - Bilqis Fathu Qodar; Willy Sri Yuliandhari (Yayasan Ilomata, 2026)
Indonesia's energy sector faces growing pressure to align financial performance with environmental sustainability, particularly in pursuit of the Net Zero Emissions agenda. Despite substantial scholarly attention, the impact of sustainability oriented practices, including green accounting disclosure, eco efficiency, and sales growth, on firm value remains inconclusive. This uncertainty is particularly pronounced in emerging economies, where sustainability reporting frameworks are still evolving and have not yet reached full maturity. This study examines how these three variables influence firm value among IDX-listed energy companies. A quantitative explanatory design was applied using panel data regression on 100 firm-year observations from 20 companies over the 2020–2024 period, selected via purposive sampling, with analyses conducted in EViews 13. Sequential Chow, Hausman, and Lagrange Multiplier tests identified the Common Effect Model (CEM) as the most appropriate specification; heteroscedasticity was addressed using CEM with White Diagonal robust standard errors. Results show that green accounting disclosure exerts a positive and significant effect on firm value (β = 1.685753; p = 0.0199), while eco-efficiency produces a significant negative effect (β = −0.509943; p = 0.0021). Sales growth is non-significant (β = 0.005196; p = 0.6174). The overall model is significant (p = 0.0038), though explanatory power is limited (R² = 0.187). These findings reveal that investors interpret sustainability signals differently: environmental disclosure is positively valued, whereas ISO 14001-based eco-efficiency is associated with reduced market valuation, underscoring the importance of distinguishing environmental reporting from environmental management practices in firm valuation.